Comparing income over feed costs in a protein premium market - Bliss, Ashley (My University, 2020)
Because dairy producers are subject to market prices, they continually strive to manage input costs and milk output to capture the largest margin. For ABC dairy, the opportunity to sell milk into a high protein market was a decision to capitalize their current herd structure. After a year supplying milk to the higher protein market, the farm desired to examine the income over feed cost to determine how the high protein group compared to the rest of the herd. The objective for this thesis is to observe the net milk income over feed cost monthly for 2019. Through understanding the milk value and feeding costs, the margin for each group was calculated on a per cow, per cow per day, and per hundredweight basis. Using daily, weekly, and monthly data from the farm’s cow feeding software and milk records, this analysis compared the performance and income over feed cost for the two groups within the herd. The results in this study showed the high protein group had a lower net milk income over feed cost of $9.13 per cow per day, compared to the rest of the herd at $9.68 per cow per day. The lower number is attributed to the different diets fed and the difference in milk price. While the high protein group shows a higher income over feed cost, this wasn’t consistent across the year. Further research could examine the relationship between butterfat and protein price or class III markets of dairy to determine if changes in these variables will help predict when and if the high protein group would have a higher net milk income over feed cost than the rest of the herd.
Keywords: Protein Market; Income over feed costs; Dairy Herd; Agribusiness; Animal Health